Finite difference model of wave motion for structural health monitoring of single lap joints. (April 2019) - Carrino, Stefano; Nicassio, Francesco; Scarselli, Gennaro; Vitolo, Raffaele
Abstract: This study is focused on the development of a finite difference model to simulate Lamb wave propagation through Single Lap Joints (SLJs). The main advantage of this model is the mathematical ability to easily reproduce the presence of a damage (debonding) as a discontinuity in velocity values. This makes our model suitable for continuous and embedded Structural Health Monitoring (SHM) of a complex structure. Numerical simulations and experimental campaigns are presented in order to validate the proposed model.